STUDY OF SERUM LEPTIN LEVEL IN PATIENTS DIABETES MELLITUS TYPE 2: IN RELATION WITH INSULIN LEVEL - SADEQ, MATEEN BAHJAT (Fırat Üniveristesi, 2020)
Amaç: Leptin gıda alımını düzenleyen bir hormondur. Adpositlerde salgılanan leptin 167 amino asitten oluşan bir proteindir. Alınan diyetin leptin direncini etkilediği bilinir. Diabetes mellitus Tip 2' de de leptin önemli role sahiptir. Bununla beraber leptin diyabet ve obezitede yükselse de, herhangi bir hastalığın nedeni değildir. Bu çalışmanın amacı tip 2 diyabetes mellitus ve sağlıklı olan hastada serum leptin düzeyini değerlendirmek ve T2DM 'de serum açlık insulin ile leptin arasındaki ilişkiyi araştırmaktır. Gereç ve yöntem: Bu çalışma kesitsel, Irak'ın Duhok şehrinde bulunan Azadi Eğitim Hastanesi Endokrin ve Diyabet Ünitesinde gerçekleştirildi. Bu çalışma 92 denekte, 70'i T2DM hastası ve 22'si diyabetik olmayan sağlıklı deneklerde gerçekleştirilmiştir. Serum leptin ELISA kullanılarak ölçüldü. Serum insulin otoanalizör Cobas E411 ile ölçüldü ve Glikatlı hemoglobin (HPLC D10) otomati kanaliz cihazı ile yapıldı. Sonuç: Çalışmamızda, diyabetik hasta grubunda leptinsan, control grubu ile karşılaştırıldığında, hasta grubunda ve hasta grubunda (20.66±11.06 µU) leptine (23.42±9.79ng/mL) (p<0.05) gore daha yüksekti. İnsüline karşı control grubuyla (12.07±5.49 µU/mL) (p <0.01). Ayrıca leptin ve insulin birbirleri ile yüksek pozitif korelasyon gösterdi (p<0.001, r= 0.479). Serum leptin ve insülin, açlık glikozu ve BMI ile önemli ölçüde ilişkilidir. Bulgular: Bu çalışmada leptin ve insülinile T2DM arasında anlamlı bir ilişki araştırılmış ve leptin ile insulin arasında da anlamlı bir ilişki bulunmuştur.

Background: Leptin is a hormone that regulates food intake. The leptin secreted in adipocytes is a protein consisting of 167 amino acids. It is known that the diet taken affects leptin resistance. In diabetes mellitus Type 2, leptin plays an important role. However, although leptin is elevated in diabetes and obesity, it is not the cause of any disease. Objective: This study aims to evaluate the level of serum leptin in Type 2 diabetes mellitus and healthy patients and to investigate the relationship between serum fasting insulin and leptin in T2DM. Material and method: Material and method: This study was carried out in cross-section, Azadi Education Hospital Endocrine and Diabetes Unit in Duhok, Iraq. This study was performed in 92 subjects, 70 patients with T2DM, and 22 patients without healthy diabetic subjects. Serum leptin was measured using ELISA. Serum insulin was measured with autoanalyzer Cobas E411 and made with glycated hemoglobin (HPLC D10) automated analyzer. Results: In our study, we investigate leptin significantly in the diabetic patient group was higher than in control subjects group, leptin in the patient group (23.42±9.79 ng/mL) against (17.01±6.84 ng/mL) with (p<0.05), and insulin in the patient group (20.66±11.06 µU/mL) against (12.07±5.49 µU/mL) in the control group with (p<0.01). also, leptin and insulin positively correlated with high significantly with each other(p<0.001, r= 0.479). Serum leptin and insulin are significantly related to fasting glucose and BMI. Conclusion: In this study, a significant relationship between leptin and insulin and T2DM was investigated and a significant relationship was found between leptin and insulin.
Diabetes mellitus tip 2 hastalarında serum leptin durumunun ve insülin düzeyiyle ilişkisinin araştırılması
Keywords: Biyokimya